Design and Development of a Water Bath Control System : A Virtual Laboratory Environment - Hasim, Norhaslinda; Md Basar, Mohd Farriz; Mohd Aras, Mohd Shahrieel (2011)
In this paper, the development of a water bath control system in a virtual laboratory environment is discussed. The system proposed is developed using LABVIEW 8.6. This project consists of three stages. The first stage is hardware development, which involves construction of interface circuit to allow communication between plant and computer. The second stage is to build the Fuzzy Logic Controller using LABVIEW software, where fuzzy set and rule base are applied. The final stage is to publish the GUI module onto the web for real-time remote control. An internet based GUI module environment of a water bath temperature control system has successfully been developed using LABVIEW software and published onto the web where it can be fully controlled using Fuzzy Logic Controller developed, and monitored by any user despite of their geographical locations, as long as they have computers with web browsers and internet connection. Thus, this will assure a better and easier understanding of certain subjects, especially control system. With such a facility, laboratory resources can be shared online, laboratory experiments can be carried out away from the site as well as outside the official working hour, and the control subject can be taught in a more meaningful and effective manner to the students.